Restorative Mediation in Environmental Investment Disputes: An Indonesian Civil Law and BIT Perspective - Danial Syah; Martin Uribe (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Foreign investment supports economic development but may also cause environmental damage, community losses, and disputes involving investors, government authorities, and affected communities. Existing Bilateral Investment Treaties and investor–State dispute settlement mechanisms primarily emphasize investor protection, while environmental restoration, civil compensation, and community participation remain limited. This study examines the legal basis for restorative mediation in environmental disputes involving foreign investors in Indonesia and develops a model integrating civil liability, environmental restoration, and investment treaty obligations. Using normative legal research, the study applies statutory, conceptual, case, comparative, and treaty-design approaches to Indonesian civil, environmental, investment, and dispute resolution laws, relevant investment treaties, and international mediation instruments. The findings show that such disputes involve not only investor–State relations but also unlawful acts, contractual liability, strict liability, ecological restoration, and compensation for affected communities. Conventional mediation is constrained by unequal bargaining power, limited community participation, confidentiality, and weak monitoring. The study proposes a Multi-Party Restorative Environmental Investment Mediation Model involving investors, government institutions, affected communities, independent experts, and mediators. The model includes environmental harm screening, responsibility mapping, stakeholder representation, independent fact-finding, restorative negotiation, legal validation, and compliance monitoring. Restorative mediation may resolve civil consequences and support environmental recovery, but it must not eliminate criminal responsibility. The model offers a balanced framework for investment protection, environmental sustainability, community rights, and State regulatory authority.